2004
DOI: 10.1083/jcb.200310015
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of caspase-4 in endoplasmic reticulum stress-induced apoptosis and Aβ-induced cell death

Abstract: Recent studies have suggested that neuronal death in Alzheimer's disease or ischemia could arise from dysfunction of the endoplasmic reticulum (ER). Although caspase-12 has been implicated in ER stress-induced apoptosis and amyloid-β (Aβ)–induced apoptosis in rodents, it is controversial whether similar mechanisms operate in humans. We found that human caspase-4, a member of caspase-1 subfamily that includes caspase-12, is localized to the ER membrane, and is cleaved when cells are treated with ER stress-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
681
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 799 publications
(708 citation statements)
references
References 55 publications
23
681
2
2
Order By: Relevance
“…NEFA induce ER stress response genes (nuclear factor κB [NFκB]) in beta cells [45] in a similar, but not identical, way to that of cytokines (IL-1β, TNF-α) [44]; these effects were shown to be more pronounced in cells exposed to palmitic than oleic acid [44,45]. TGs that are rich in saturated fatty acids remain in the ER of cells and could trigger induction of ER stress response proteins, leading to apoptotic death [46]. Recently it has been shown that factors related to oxidative stress (reactive oxygen species and nitric oxide) and palmitate-derived ceramides are not causative factors for loss of GSIS following chronic exposure to NEFA [37].…”
Section: Discussionmentioning
confidence: 99%
“…NEFA induce ER stress response genes (nuclear factor κB [NFκB]) in beta cells [45] in a similar, but not identical, way to that of cytokines (IL-1β, TNF-α) [44]; these effects were shown to be more pronounced in cells exposed to palmitic than oleic acid [44,45]. TGs that are rich in saturated fatty acids remain in the ER of cells and could trigger induction of ER stress response proteins, leading to apoptotic death [46]. Recently it has been shown that factors related to oxidative stress (reactive oxygen species and nitric oxide) and palmitate-derived ceramides are not causative factors for loss of GSIS following chronic exposure to NEFA [37].…”
Section: Discussionmentioning
confidence: 99%
“…Human caspase-4 is a potential homolog of murine caspase-12 involved in ER stress (Hitomi et al, 2004). As shown in Figure 2b, edelfosine treatment induced caspase-4 activation, as assessed by cleavage of procaspase-4 into the 20-kDa active form.…”
Section: Induction Of Apoptosis By Edelfosine and Other Alps In Humanmentioning
confidence: 92%
“…Nevertheless, ER stress sensors do not directly cause cell death, but rather initiate the activation of downstream molecules, such as CHOP (C/EBP homologus protein)/ growth arrest and DNA damage-inducible gene 153 (GADD153) or c-Jun NH 2 -terminal kinase (JNK), which further push the cell down the path of death. Three main pathways of ER stress-induced apoptosis are known, namely: (1) upregulation of the transcription factor CHOP/GADD153 (Ron and Habener, 1992); (2) JNK activation (Urano et al, 2000); (3) activation of caspase-12 in murine systems or caspase-4 in human cells (Hitomi et al, 2004). These three pathways all end in caspase cascade activation followed by the induction of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-4 is increased in AD brains, suggesting that this caspase may play a role in ER stress-induced cell death. 25 Recent studies on the UPR revealed increased levels of Bip/Grp78 and the protein kinase, Perk in AD brain. 44 This shows the occurrence of ER stress in AD although the initial changes in these UPR mediators may reflect neuroprotection rather than nerve cell degeneration.…”
Section: Er Stress and Admentioning
confidence: 99%
“…10,24 It is possible that other caspases take over the function of caspase-12 in humans, as suggested for the human caspase-4. 25 However, the role of caspases-12 and -4 as initiators of ER stress-induced cell death is a matter of current debate. 24 Procaspase-2 and a novel procaspase-8 isoform are also associated with the ER in some cell types.…”
Section: Introductionmentioning
confidence: 99%